Surface composition, adhesion strength and biocompatibility activity of CoCrMo-Hydroxyapatite composite - Nurul Akmal, Che Lah; Mas Ayu, Hassan; Rosdi, Daud (Elsevier Ltd, 2025)
Hydroxyapatite (HA) has been considered one of the most efficient surface modification implant components for enhancing osteointegration. However, post-traumatic inflammation or swelling stands out as one of the substantial obstacles in reconstructive surgery involving Cobalt-Chrome-Molybdenum (CoCrMo) orthopaedic implants. Continuous efforts have been made to increase the success towards improving the surface-modified CoCrMo-HA interface and its impact on ion release, the primary mechanisms of degradation. Herein, the present study endeavours to report a detailed surface composition analysis of fabricated CoCrMo-HA alloys, highlighting the changes in surface bioactivity and metal ion release, as influenced by the sintering temperatures. Notably, CoCrMo-HA850 alloy sintered at 750 °C disclosed the most compromised system for better surface modification, improved biocompatibility and metal ion release activity properties. Parallelly, a comparative analysis of scaffolds composed of the scaffold poly lactic acid (PLA) reinforced with HA, forming CoCrMo-PLA/HA composites and another sample incorporating foreign ion magnesium, Mg with HA forming CoCrMo-Mg/HA composite. The incorporation of PLA and Mg into CoCrMo-HA structures yields distinct nucleation, cracking and propagation features due to varying system stabilities. The discoveries reported in this work are crucial for advancing understanding and to re-think improved CoCrMo-HA systems for future applications in bone regeneration implants and scaffolds.